Pembinaan Karakter Peduli Lingkungan Melalui Pengolaan Sampah Anorganik Di Kelas V SD Negeri 6 Lawa - La Sisi; Chairan Zibar L. Parisu; Itsnain Alfajri Husain (Prodi PGSD Unsultra, 2025)
The problem at SD Negeri 6 Lawa is that many students still don't care about the environment and develop efforts to repair the natural damage that has occurred. One of the causes of environmental damage is inorganic waste. Therefore, coaching needs to teach students how to process inorganic waste. The objectives of this research are to find out: 1) What is the character of students who care about the environment at SD Negeri 6 Lawa 2) How inorganic waste is managed at SD Negeri 6 Lawa 3) How to develop environmentally caring character through processing inorganic waste at SD Negeri 6 Lawa. The type of research used by the research is qualitative research with the main data sources being principals, class teachers, arts and culture teachers and students at SD Negeri 6 Lawa. The data collection techniques used are observation, interviews, documentation. The validity of the data was tested by technical triangulation and source triangulation. The data obtained is analyzed using steps, namely data reduction, data presentation, conclusions. From the results of the research that has been carried out, it can be concluded that: 1) the students' character towards caring for the environment at SD Negeri 6 Lawa, most of the students have developed a character towards the environment, such as cleaning the classroom and throwing away organic and inorganic waste; 2) And the teacher's efforts in forming the student's character by providing methods of example, habits, rewards, and socialization of environmental care directly or indirectly; 3) Inorganic waste processing is carried out through several stages, namely planning, implementation and evaluation; 4) Products from inorganic waste processing consist of flower pots, lanterns, pencil boxes, flower boxes, mini waste boxes.